Representations of Migrant Workers in Malayalam Movies - S H, Sidharth. (IISER Mohali, 2020)
Different waves of migration play an essential role in the economic development of the south Indian state of Kerala. The outmigration of Malayalees has resulted in a shortage of labor power in the state, which led to the wave of in-migration of workers from other Indian states. At present, workers mainly from the north and north-eastern states of India serve as the workforce of god's own country. Cinema, as a visual-auditory narrative, can communicate with the mass audience and influence the formation of opinions in a society. This study analyzes various kinds of approaches that get represented through the migrant worker characters and themes related to them, in Malayalam movies. While stereotypical images and themes get reproduced, the real-life of migrant workers, the state's fuel for development, often goes unrepresented.
Keywords: Malayalam Movies; Masala Republic; Regional cinema